Strategies for accessing regulatory expertise in post-reform electricity sectors: feedback from 9 French-speaking sub-Saharan African countries - (:unkn) unknown (My University, 2024)
Following electricity sector’ reforms, sub-Saharan African (SSA) countries have established sectoral regulatory agencies. They are responsible for supervising the activity and the actors in a new sectoral context characterized by more or less important organizational changes. In this regard, the basic conditions of the regulatory framework in SSA countries have undergone significant changes as well which have justified the emergence of a new regulatory paradigm and the need of new regulatory skills. This article analyzes the strategies developed by electricity sector regulators in 9 SSA countries in the necessary quest for regulatory expertise in this new context. This paper proposes an analytical framework for possible options in the construction of new expertise in the regulation of the electricity sector in SSA, applies this framework to 9 countries and highlights a variety of responses due to the specificities of national contexts.
Keywords: African Research